DETERMINING THE OPTIMAL SITE LOCATION OF GNSS BASE STATIONS - HAN, JEN-YU; WU, YU; LIU, ROU-YU (Boletim de Ciências Geodésicas, 2012)
The relative positioning technique plays an essential role in Global Navigation Satellite System (GNSS) surveys. Simultaneous observation at base and rover stations eliminates the majority of error sources thus the quality of a positioning solution can be substantially improved. However, topographic obstruction is still a key issue affecting positioning quality. In this study, an integrated approach for analyzing the impact of topographic obstruction on GNSS relative positioning has been developed. By considering varied satellite geometry according to actual terrain variation, this approach can be used to realistically determine satellite visibility condition for a specific base station with respect to any rover station. Furthermore, a base station quality index (BSQI) is proposed as an explicit indication of the sufficiency in a relative positioning. By incorporating the proposed approach, one can immediately identify an optimal site location for a GNSS base station with subsequent GNSS field survey thus achieved in a more reliable and cost-efficient manner.